Proses Pelapisan Permukaan Spesimen Dari Bahan ABS Yang Dibentuk Melalui Rapid Tooling - Riyanto, Rachman Rio (2016)
Information about the results of the 3D printing process in Indonesia is still low as the level of roughness of objects generated from the process. Such information is important to note , that the products will be used in accordance with the expected goals . The aim of this study was to determine the level of roughness of ABS plastic material 3D printer products with fill density of 20% and 50 % of uncoated , coated and coated Chrome Coating Resins Gelcoat . In the process of this test using material Acrylonitrile Butadiene Styrene ( ABS ) formed for specimen testing roughness and tested with test equipment roughness ( Roughness Tester Type TR120 with ISO standards ) with a variety of materials ABS with fill density of 20% without a coating , the coating of paint chrome and the upholstery Rengel . Fill density of 50 % without a coating , the coating paints and coatings Chrome Rengel . From the test results are obtained roughness values Roughness Average ( Ra ) . Roughness of ABS material 3D printer products with fill density of 20% uncoated generate Ra values of 10.291 μm , whereas Chrome Coating of 1.780 μm and coated Gelcoat Resin of 0,849 lm. Roughness of ABS material 3D printer products with fill density of 50 % uncoated generate value Ra of 5.164 μm , whereas Chrome Coating of 1.115 μm and coated Gelcoat Resin of 0.529 lm. From these data the optimal kehalusanyang level in the specimen with 50 % fill density and Gelcoat Resin coated .